Situación epidemiológica de la coccidia (ISOSPORA SP) en caninos atendidos en la clínica veterinaria terranova de la ciudad de Popayán en el periodo de febrero a junio del 2021. (2021)
In veterinary medicine, the canines have had various functions that make a bond important with the human being, which accompaniment is one of the most important. This is why pet owners, in this case canines, these owners watch for his care which is based on health, food and affection. This lifestyle every day is bigger, that is why the veterinarian plays a fundamental role in keep the welfare of pets in the best conditions. The topic to be addressed in this study is coccidia, which is known as a parasite unicellular intestine of the genus Eimeria and Isospora that is clinically characterized by generate a picture in enteritis or inflammation of one or more portions of the intestine, changing excessive diarrhea, which triggers high dehydration, a great loss of erythrocytes, which generates a picture of anemia that if not treated in time leads to the death of the pet. Coccidia in canines has become a very important query in veterinarians, since that climate change helps the rapid spread of this parasite. This study was carried out in the northern area of ​​the city of Popayán, Cauca, exactly in the Terranova veterinary clinic, where 111 cases of canines treated in is The main action of this work was to find through coprological samples the presence of this parasite in the physical environment inhabited by each canine. In the same order of ideas is intended to identify the degree of destruction of this organism and the level of affectation according to the range of ages established for the pet. once was performed the collection of samples, with the support of the LINALAB clinical laboratory, processed the elements to obtain the results that supported the purpose of this research.